Simian virus 40 large T antigen host range domain functions in virion assembly. - Spence, S L (1994)
The simian virus 40 (SV40) T antigen host range mutants dl1066 and dl1140 display a postreplicative block to plaque formation which suggests a novel role for T antigen late in the viral life cycle. The host range mutants dl1066 and dl1140 are able to grow in and plaque on BSC but not on CV1 monkey kidney cells, a normally permissive host. Previous work showed that in CV1 cells infected with dl1066 and dl1140, levels of viral DNA replication and of late capsid protein accumulation were only slightly reduced and the failure to accumulate agnoprotein was not likely to be the major factor responsible for the mutants' growth defect. Here we show that the host range mutants are defective in the assembly of viral particles. SV40 assembly proceeds as the progressive conversion of 75S viral chromatin complexes to 200S-240S assembled virions. When virus-infected cell extracts are separated on 5 to 40% sucrose gradients, wild-type extracts show the greatest accumulation of viral late protein in the 200S-240S fractions corresponding to the assembled virus peak and lesser amounts in the 75S-150S fractions corresponding to immature assembly intermediates. The host range mutants dl1066 and dl1140 grown in nonpermissive CV1 cells, however, failed to assemble any appreciable amounts of mature 200S-240S virions and accumulate 75S intermediates, whereas in permissive BSC cells, levels of assembly were more slightly reduced than those of the wild type. Analysis of the protein composition of gradient fractions suggests that SV40 assembly proceeds by a mechanism similar to that proposed for polyomavirus and suggests that the host range blockage may result from a failure of such mutants to add VP1 to 75S assembly intermediates.